The Potential of Bekasi “Eduforest” urban forest in cultural environmental services - Tsamarah Nada Saninah; Rachmad Hermawan; Yudi Setiawan; Tania June (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2023)
Setu Subdistrict, Bekasi Regency is an area designated as urban forest development for providers of cultural environmental services. The purpose is to identify the community's perceptions, motivations, and preferences around the urban forest. Primary data collection by questionnaire to 31 people was determined purposively and analyzed quantitatively using a 4-point Likert Scale. Calculation of air temperature and humidity, thermal comfort, biomass with allometric methods, and CO2 absorption to support recommendations for attractions. The results show that community knowledge, benefits, and functions of urban forests are well known. People visit urban forests because they provide comfort and good air quality so that they are physically and mentally healthy. Community preferences are in the form of harvesting honey and developing urban forests together so that they can participate further. The potential of the urban forest in cultural environmental services can be developed through the provision of massive information and counseling, the development of tourist attractions in the form of forest healing, educational, and culinary tourism, also panoramic and landscape attractions. With the relative humidity of 60% and the thermal comfort of 25.2 oC, categorized as quite comfortable, the development of health therapy tourism can be considered.